Evidence based review on the effect of Islamic dietary law towards human development - Md Sawari, Siti Salwa; Ghazali, Mohd Al'Ikhsan; Ibrahim, Mohd Burhan; Mustapha, Nurul Izzah (MCSER-CEMAS-Sapienza University of Rome, 2015)
Food is necessary for human’s survival. Human beings become more health-conscious in consuming foods and drinks. This is to promote healthy lifestyle and prevent from illness caused by food consumption. Healthy lifestyle starts since the beginning of the time and dietary practices is connected with religious practices. Islam has acknowledges the importance of consuming food to nourish the body and mind. In this paper researcher will explain the connection of consuming food according to Islamic rules towards human development; intellect, akhlak, moral and psychology. Result from the analysis indicated that, consumption of food does surely affect human development on akhlaq, moral and psychology. If one choose an unhealthy lifestyle or consume haram food which Allah has prohibited, one may suffer health difficulties, resulting in stress and exhaustion physically and spiritually. Establishing Islam does not only means establishing mosques, Islamic centers and schools, but also establishing Muslims economically, politically as well as physically. When we put good things in our body, then only good things will come to our life. Allah’s command to consume halal food is not merely related to Ibadah which entails the relationship between He and His creations, but also has wisdom behind it that is surely giving benefits to humankind. Halal food consumption can lead people to healthy lifestyle and give positive growth to human development.